A systematic review for organizing hackathons and code camps in Covid-19 like times: Literature in demand to understand online hackathons and event result continuation - Happonen, A. (Institute of Electrical and Electronics Engineers Inc., 2021)
The hackathons related systematic literature review findings, from the past 15 years, show that academics mostly focus on giving overview, describing and explaining the events. It also seems to be quite popular to present an overview of event arrangements. The research, which appears to be missing, is the new style of hackathons, which were a requirement for online hackathons and remote events because of the social distancing, e.g., what covid-19 did demand from global society. By core design, hackathons have always been social gatherings and innovation events. Especially in these exceptional times with social distancing requirements, hackathon organizers turned towards online models. As this is not the original way these events have been organized, it was hard to get the best practices to how to proceed as there are few to none general guidelines and models for online/remote hackathons. By studying the current academic literature, our systematic literature review concludes that contemporary academic literature does not give too much guidance either. This review concludes that more practical, on-site, and educational problem-based development research studies about online and remote hackathon events are needed. Especially research on means and tools to utilize to organize them and handle exceptions and be successful in new normal. Â© 2021 IEEE.